Nanotechnology Intervention to Alleviate Disease-Specific Dysbiotic Microbiome - Dr. Suyash Arunrao Kathade (The Bioscan, 2025)
Dysbiosis of the microbiome, characterized by an imbalance in the composition and functionality of microbial communities, has been linked to various diseases and disorders. The emerging field of nanotechnology offers promising strategies to address these dysbiotic conditions and restore microbial homeostasis. This abstract explores the application of nanotechnology interventions in alleviating disease-specific dysbiotic microbiomes. Nanoparticles in delivery systems offer distinctive opportunities for the targeted and regulated administration of medicinal medicines to specific areas within the microbiome. Functionalized nanoparticles can be engineered to specifically interact with dysbiotic microbial populations, selectively delivering antimicrobial agents, probiotics, or prebiotics to restore a healthy microbial balance. The Metabolites and inflammatory biomarkers, enabling rapid and accurate diagnosis of dysbiotic conditions, provide critical insights into disease progression, facilitate personalized treatment strategies, and monitor treatment efficacy. However, the translation of nanotechnology-based interventions for dysbiotic microbiomes into clinical applications requires addressing concerns related to safety, biocompatibility, and long-term effects. Comprehensive investigations of potential nanomaterial toxicity and environmental impacts are essential for ensuring the responsible development and deployment of nanotechnology in microbiome therapeutics. Further research and development efforts are necessary to advance these interventions, benefiting patients suffering from dysbiotic microbiome-related conditions. KEYWORDS Microbiome, Disease, Health, Probiotics, Immunomodulation.